Introduction to the Special Issue on "Analysing the Politics of Health Policy Change in Low- and Middle-Income Countries: The HPA Fellowship Programme 2017-2019" - Lucy Gilson; Zubin Cyrus Shroff; Maylene Shung-King (Kerman University of Medical Sciences, 2021)
This special issue presents a set of seven Health Policy Analysis (HPA) papers that offer new perspectives on health policy decision-making and implementation. They present primary empirical work from four countries in Asia and Africa, as well as reviews of literature about a wider range of low- and middle-income country (LMIC) experience.